2015
DOI: 10.3390/ijms160510389
|View full text |Cite|
|
Sign up to set email alerts
|

Subcellular Sequestration and Impact of Heavy Metals on the Ultrastructure and Physiology of the Multicellular Freshwater Alga Desmidium swartzii

Abstract: Due to modern life with increasing traffic, industrial production and agricultural practices, high amounts of heavy metals enter ecosystems and pollute soil and water. As a result, metals can be accumulated in plants and particularly in algae inhabiting peat bogs of low pH and high air humidity. In the present study, we investigated the impact and intracellular targets of aluminum, copper, cadmium, chromium VI and zinc on the filamentous green alga Desmidium swartzii, which is an important biomass producer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 32 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…It has been also reported that mitochondria were underdeveloped in the Brassica napus seedlings that were exposed to 400 µM Cr as compared seedlings exposed to control conditions [41,120]. The ultrastructural investigations also revealed that Cr(VI) stress alters plastid structure, more specifically, chloroplast, with a spherical and contracted morphology [120][121][122][123]. The irregular shape and size of the chloroplast with contained large plastoglobuli and starch grains were reported in Spirodela poyrhiza seedlings that were exposed to high Cr(VI)-level [23].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 85%
See 1 more Smart Citation
“…It has been also reported that mitochondria were underdeveloped in the Brassica napus seedlings that were exposed to 400 µM Cr as compared seedlings exposed to control conditions [41,120]. The ultrastructural investigations also revealed that Cr(VI) stress alters plastid structure, more specifically, chloroplast, with a spherical and contracted morphology [120][121][122][123]. The irregular shape and size of the chloroplast with contained large plastoglobuli and starch grains were reported in Spirodela poyrhiza seedlings that were exposed to high Cr(VI)-level [23].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 85%
“…The irregular shape and size of the chloroplast with contained large plastoglobuli and starch grains were reported in Spirodela poyrhiza seedlings that were exposed to high Cr(VI)-level [23]. Cell membrane injury, disruption of cytoplasm, and vacuole upon Cr exposure are frequently reported [23,120,121]. Table 5 summarizes the ultrastructural changes reported in the different plant species exposed to Cr-stress.…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 98%
“…Excessive absorption, however, prevented the growth of strain S4 to some extent and led to limitations in the dry weight of its mycelium. There are two main mechanisms that can be used to interpret Al resistance in microbes: one is the chelation of Al outside of the cell via the cellular secretion of special compounds and the other is the sequestration of Al inside of the cell via the formation of complexes [27][28][29][30][31]. According to our experimental results, the majority of Al 3? was still retained in the medium (data not shown), implying that strains S4 and S7 possibly resisted Al stress by preventing soluble Al from entering the cells.…”
Section: Discussionmentioning
confidence: 81%
“…Variable palisade parenchyma was first negatively impacted on the presence of the caprylic acid, which was an important apparatus linked to leaf protection against high light intensity (Tuffi et al, 2008). Caprylic acid affects directly leaf photosynthetic process, causing a decrease in the availability of metabolites and in the growth rate of plant (Pasqualini et al, 2002;Andosch et al, 2015). The stress response is first recognizable at the metabolic level; if the exposure to stress factors persists, then changes are recognizable at the microscopic level and finally are expressed as visible, morphological changes.…”
Section: Discussionmentioning
confidence: 99%